Excessive Daytime Sleepiness Is Associated With Non-motor Symptoms of Multiple System Atrophy: A Cross-Sectional Study in China - Wang, Hui; Tang, Xiangdong; Zhou, Junying; Xu, Yanming (Frontiers in Neurology, 2022)
Abstract Objectives: Excessive daytime sleepiness (EDS) in multiple system atrophy (MSA) has received scant attention in the literature, the present cross-sectional study aimed to investigate the prevalence of EDS and its potential risk factors among Chinese patients with MSA. Methods: A total of 66 patients with MSA (60.6% males) were consecutively recruited. Eighteen patients (27.3%, 13 men) with Epworth Sleepiness Scale score > 10 were defined as having EDS. Demographic, motor (Unified Multiple-System Atrophy, UMSARS) and non-motor symptoms (Non-Motor Symptoms Scale, NMSS), and sleep parameters (polysomnography, PSG) were compared between MSA patients with and without EDS. A logistic regression analysis was used to calculate the risk factors of EDS in patients with MSA. Results: There were no significant differences in age, sex, MSA onset age, disease duration, MSA sub-type, and motor symptom severity between MSA patients with and without EDS. However, compared with the MSA patients without EDS, their counterparts with EDS had higher scores of NMSS (65.3 ± 23.1 vs. 43.4 ± 25.3, P = 0.002), Hamilton Anxiety (HAMA) (15.3 [10.3‒20.0] vs 9.5 [3.0‒15.0], P = 0.006), Hamilton Depression (HAMD) (13.7 [12.5‒17.8] vs 9.0 [4.0‒13.0], P = 0.015), and Fatigue Severity Scale (29.8 [17.3‒47.8] vs 18.7 [10.3‒21.8], P = 0.040). Conversely, the patients with EDS had lower score of Mini-Mental State Examination (MMSE) (23.3 [20.3‒27.0] vs 25.7 [22.0‒29.0], P = 0.023). Similarly, there was a significantly lower percentage of N3 sleep (0.3 [0‒0] vs 2.0 [0‒0], P = 0.007) and a higher apnea-hypopnea index (AHI) (30.5 [14.5‒47.8] vs 19.3 [5.0‒28.7], P = 0.034) in patients with EDS. After adjusting for age, sex, disease duration, MSA sub-type, and UMSARS score, the odds ratio (OR) (95%CI) of EDS was higher while increasing scores in FSS (1.06[1.02-1.11]), HAMA (1.16[1.04-1.28]), HAMD (1.13[1.02-1.25]), NMSS (1.04[1.01-1.07], and AHI (1.03[1.00-1.10]). The OR of EDS was lower while MMSE score increasing (0.85[0.72-1.00]). Conclusions: The presence and severe of EDS may be significantly associated with the non-motor dysfunction including fatigue, anxiety, depression, cognitive dysfunction and sleep related breathing disorders, but not with the motor dysfunction in MSA.